2015
DOI: 10.1007/s00590-015-1694-2
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of tibial torsion by magnetic resonance imaging in children: the comparison of three different methods

Abstract: MRI-based tibial torsion measurements were reliable and reproducible for all three methods. But we think that the anterior talus angle and the posterior malleolar angle are easier and more successful in determination of the tibial torsion. Also, both T1- and T2-weighted images can be used successfully for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In the group of reduced FT as well as in the group of excessive FT, tibial torsion can be considered as normal with a mean torsion of 29 ± 7° and 33 ± 5° respectively, although the range of so called normal tibial torsion is wide with mean values in the literature of 19–40°. 22,3436 The difference of tibial torsion of the 2 groups was not significant ( p = 0.158) supporting the results of Reikerås et al, 36 who found no compensatory external rotation of the lower leg in cases of increased FT. Also Waidelich et al 35 found no correlation between femoral and tibial torsion. In contrast to these results, Tönnis and Heinecke 1 suspected a relationship between rotation of femur and tibia.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the group of reduced FT as well as in the group of excessive FT, tibial torsion can be considered as normal with a mean torsion of 29 ± 7° and 33 ± 5° respectively, although the range of so called normal tibial torsion is wide with mean values in the literature of 19–40°. 22,3436 The difference of tibial torsion of the 2 groups was not significant ( p = 0.158) supporting the results of Reikerås et al, 36 who found no compensatory external rotation of the lower leg in cases of increased FT. Also Waidelich et al 35 found no correlation between femoral and tibial torsion. In contrast to these results, Tönnis and Heinecke 1 suspected a relationship between rotation of femur and tibia.…”
Section: Discussionsupporting
confidence: 67%
“…The angle (°) between these 2 lines was defined as FT. Tibial torsion was assessed by measuring the angle (°) between a tangent on the posterior tibia on the first axial slice where the fibular head was visible and a line connecting the centres of the anteroposterior diameters of the two malleoli at the level of the ankle joint. 21,22 Tuberosity to trochlear groove distance (TTTG), patellar tilt and patella bisect offset were measured on transverse MRI images. TTTG was defined as the distance (mm) between a line through the deepest point of the trochlear groove and the centre of the tuberosity keeping both lines perpendicular to the tangent of the posterior condyles.…”
Section: Methodsmentioning
confidence: 99%
“…Several techniques for quantifying torsional disorders of the tibia have been described. Although some suggest assessment using biplanar radiography or magnetic resonance imaging ( 6 ), computed tomography (CT) imaging is currently considered the gold standard ( 7 ). CT's advantages are its widespread availability, proven accuracy, short examination time, and cost-effectiveness ( 8 ).…”
Section: Introductionmentioning
confidence: 99%